Batas Usia Capres-Cawapres Dalam Keputusan MK No. 90/PUU-XXI/2023 Dan Implikasinya Terhadap Dinasti Politik Perspektif Fikih - Aykar, Naslul; Muhammad Arfan Ahwadzy (Syariah: Journal of Fiqh Studies, 2024)
The Regulation on changing the age limit for presidential and vice presidential candidates by the Constitutional Court (MK) No. 90/PUU-XVIII/2023 has drawn pros and cons, with some people supporting and some rejecting it because it is considered to have the potential to worsen political dynamics, especially regarding the practice of political dynasties. Based on this reality, this study aims to assess whether the Constitutional Court's decision is in line with the Islamic jurisprudence view and to explain the Islamic jurisprudence view regarding the potential for strengthening political dynasties that may arise as a result of this policy. This study uses a literature review approach. The main sources used are the Qur'an, Hadith, the at-turās pole, and the Constitutional Court's Decision No. 90/PUU-XXI/2023. The analysis was carried out qualitatively, with a comparative approach to compare the Islamic jurisprudence perspective on age as a leadership criterion with provisions in positive law. The results of this study show that from a fiqh perspective, the change in the age limit for presidential and vice presidential candidates in the Constitutional Court's decision is in line with Islamic principles in terms of implementing policies that are beneficial. However, even though the Constitutional Court's decision is legally valid, Islamic jurisprudence does not justify the existence of external factors behind the decision, especially those related to conflicts of interest that have the potential to strengthen the practices of political dynasties. The practice of political dynasties is contrary to the Islamic jurisprudence view, which prioritizes governance and is not centered on a handful of groups. Therefore, the government must ensure the existence of regulations that can prevent the dominance of political dynasties and guarantee the election of quality leaders.